Research Themes, Authors, and Methodologies in the Journal of Applied Communications: A Ten-Year Overview - Leslie D. Edgar; Tracy Rutherford; Gary E. Briers (Journal of Applied Communications, 2009)
The Journal of Applied Communications ( JAC) has been a primary outlet of agricultural communications research and professional scholarship—a claim validated by a survey of professionals in the field. The purpose of this study was to assess ten years of JAC to determine primary and secondary research themes, frequent primary and secondary research themes by year, prolific authorship, and research methods and types reported, using a mixed-methods design. Analyzed in the study were 91 research and/or professional articles with research methodologies published from 1997 through 2006. The research identified twenty-one primary research theme areas and 28 secondary research theme areas. A compiled list of primary and secondary research theme areas and frequent themes identified by year are reported. JAC authors were identified totaling 222 contributors; Tracy Irani and Ricky Telg (13.2%) were the most prolific authors. A majority of the articles (65.9%) employed quantitative research methods, and survey methodology (47.3%) was the most common data collection measure. Research themes appear cyclic, with specific themes moving in and out of primary and secondary areas, which may contribute to research theme diversity. Research must continue to determine whether cycles exist; if cycles do indeed exist then focus should be placed on determining cycle depth and the influence on research in agricultural communications as an integrated specialization area of agricultural education. This research should be used comparatively with priority areas identified in the National Research Agenda: Agricultural Education and Communication, 2007–2010, to determine where future research might be focused.
Keywords: Journal of Applied Communications ( JAC); professionals; agricultural education; articles; communications; Methodologies